Individual Morality As Moderating The Influence Of Good Corporate Governance Implementation And Internal Control On Fraud Prevention In The Regional Financial And Assets Management Agency Of Badung Regency - Komang Sri Widiantari; Ni Kadek Diah Yonita Bella (UNHI Press, 2023)
The purpose of this study was to determine the effect of implementing good corporate governance, internal control on fraud prevention with individual morality as moderator carried out at the Badung Regency Regional Financial and Asset Management Agency.The population of this research is 96 employees. The sampling technique used in this study is the saturated sample technique. The sample used in this study was the entire number of employees of the Badung Regency Regional Financial and Asset Management Agency as many as 41 respondents. The analytical method used in this research is MRA (Moderad Regression Analysis), classic assumption test, coefficient of determination, f test and t test.The results showed that the variables of good corporate governance and internal control had a positive effect on fraud prevention and individual morality was able to strengthen the relationship between good corporate governance and internal control on fraud prevention.